A framework of online-merge-offline (OMO) classroom for open education: A preliminary study. Issue 2 (5th December 2019) - Xiao, Jun; Sun-Lin, Hong-Zheng; Cheng, Hsu-Chen
Abstract : Purpose: The purpose of this paper is to propose a design of online-merge-offline (OMO) classroom for open education with design principles related to practical issues of teachers' teaching, students' learning and schools' management. Design/methodology/approach: Three stages were covered: drafted an OMO classroom framework, built a sample classroom and explored end-users' experience. First, authors searched for and reviewed previous studies and related cases to draft an OMO framework. Second, a classroom, consisted of wireless devices, cloud-based services, Internet of Things terminals, ergonomics furniture, and comprehensive data management and analysis services, was built in Shanghai Open University. Third, invited 11 students', 18 teachers' and 9 school managers' perspectives were collected and analysed by surveys and interviews. Findings: All student participants responded positively in terms of learning experience in the classroom. They not only engaged in classroom activities such, but also accessed needed learning materials and interacted with teachers and peers anytime anywhere via mobile devices. Similarly, most teachers (90 per cent) made positive responses because of flexibility of teaching strategies and learning activities and expressed willingness to use the classroom in the future (94.4 per cent). In addition, more than 78 per cent of managers positively commented on the design of classroom, interaction effects and effective management. Visualised data allowed them to timely monitor status of facilities, comprehensively understand users' behaviour and issues, make necessary decision with scientific evidence. Research limitations/implications: The framework and classroom not only provide teachers, students, school managers and researcher with a better understanding of innovative open education, but also indicate the key role of objective-oriented and data-driven issues for further work. Originality/value: To meet needs of teachers, students, managers and researchers in today's open education, an OMO classroom was built in Shanghai Open University based on the proposed Objective-Oriented Pedagogy-Space-Technology (OPST) framework. The framework provides readers (especially teachers and administrators of open-education institutes, staff of information centres and ed-tech researchers) with a better understanding of innovative instruction and effective management, and the originally designed classroom can be a practical and illuminating example.